Postmenopausal Vaginal Microbiome and Microbiota - Oliveira, Nayara Santos de; Lima, Ana Beatriz Feijão de; Brito, Juliana Carvalho Regino de; Sarmento, Ayane Cristine Alves; Gonçalves, Ana Katherine Silveira; Eleutério, José (Frontiers in Reproductive Health, 2022)
The ovulatory cycle has a significant influence on the microbial composition, according to the action of estrogen and progesterone on the stratified squamous epithelium, due to an increase in epithelial thickness, glycogen deposition, and influence on local immunology. The 16S rRNA gene amplification and pyrosequencing study demonstrated that healthy women have community state types (CST), classified as; type “L,” with a predominance of Lactobacillus crispatus, type II, with a predominance of Lactobacillus gasseri, type III, where Lactobacillus iners predominates, and type V with a predominance of Lactobacillus jensenii. Type IV does not identify lactobacilli but a heterogeneous population of bacteria. There seems to be a relationship between increased vaginal bacterial diversity and poverty of lactobacilli with the complaining of vaginal dryness. With menopause, there appears to be a reduction in lactobacilli associated with higher serum levels of follicle-stimulating hormone (FSH) and lower estrogen levels. The evaluation of Gram-stained vaginal smears in postmenopause women must take into account the clinical-laboratory correlation. We should observe two meanly possibilities, atrophy with few bacterial morphotypes, without inflammatory, infiltrate (atrophy without inflammation), and atrophy with evident inflammatory infiltrate (atrophy with inflammation or atrophic vaginitis). The relationship between the microbiome and postmenopausal vulvovaginal symptoms seems to be related to the bacterial vaginal population. However, more robust studies are needed to confirm this impression.